E-commerce layout design (E-LAD) using mobile application for non-IT user / Asyraf Shahzwan Muhamad Azizon and Dzulkarnaen Ismail - Muhamad Azizon, Asyraf Shahzwan; Ismail, Dzulkarnaen (2024)
This study explores the development of a mobile application tailored for non-designers and non-IT users in the construction industry. The primary objective of this research is to innovate a software solution that facilitates layout design, construction material cost estimation, and information technology integration in construction projects. Specifically, the study aims to (1) identify existing mobile applications that cater to layout design for users without design or IT expertise, (2) assess the challenges and issues these users face in utilising such technologies, and (3) propose a marketable IT mobile application concept for construction management, focusing on design and build projects. The research methodology includes a desk study and the simulation of a product prototype. Through a comprehensive literature review and detailed analysis, the study evaluates the performance of current mobile layout design applications, highlighting their features, limitations, and the materials they employ. The proposed innovation addresses the evolving construction cost estimation and design needs, offering users greater flexibility in designing their dream homes. The findings demonstrate that the new application can significantly enhance information provision in construction and better adapt to varying user needs and preferences.